Local Variance in the Crime Drop: A Longitudinal Study of Neighbourhoods in Greater Glasgow, Scotland. (5th April 2017) - Bannister, Jon; Bates, Ellie; Kearns, Ade
Abstract: This paper reports on a novel longitudinal study of local variation in the decline of recorded crime in Greater Glasgow, United Kingdom. We deploy group trajectory analysis (exploring spatial autocorrelation with Local Moran's I) and comparison of means to explore the underlying characteristics and trajectories of neighbourhoods over time. The research finds marked distinction in the level of crime and trajectories of different neighbourhood crime groups. Neighbourhood crime trajectories with high or low levels of crime exhibit spatial clustering and significant distinction in their characteristics. There is more limited spatial patterning, though still clear distinction between the characteristics of neighbourhood crime groups that exhibit different crime trajectories. We consider the research and policy implications of these findings.